Diagnosing latent tuberculosis infection in haemodialysis patients: T-cell based assay (T-SPOT.TB) or tuberculin skin test? - ARIKAN, İZZET HAKKI (OXFORD UNIV PRESS, 2012)
Background. The international guidelines recommend screening haemodialysis (HD) patients for latent tuberculosis infection (LTBI). The aim of this study is to compare the diagnostic utility of tuberculin skin test (TST) with an interferon-gamma-based assay (T-SPOT.TB) for the diagnosis of LTBI in HD patients. Methods. A total of 411 patients [233 male (57%), mean age 56 +/- 16 years] in five HD centres were prospectively tested by TST and T-SPOT.TB assays. A total of 302 patients (75%) had Bacillus Calmette-Guerin vaccination scar. Results. LTBI was detected in 39 and 61% of patients by one-step TST and T-SPOT.TB, respectively. The booster phenomenon determined additional 60 (25%) LTBI among 243 patients. Overall, 218 (53%) patients showed a positive reaction to TST after performing the two-step TST. Among 250 one-step TST negative patients T-SPOT.TB assay was positive in 118 (47%). Of 158 patients with a positive one-step TST, T-SPOT.TB was negative in 34 (22%). On the other hand, T-SPOT.TB was negative in 16 (27%) of boosted patients. T-SPOT.TB was negative in 50 (23%) of overall TST-positive patients and positive in 71 (39%) of TST negative ones. Multivariate logistic regression analysis revealed that male gender was independently associated with positive T-SPOT.TB, and positive T-SPOT.TB was inversely associated with the presence of BCG vaccine scar, serum albumin level and HD duration. Annual conversion rates were 12 and 32% for TST and T-SPOT.TB tests, respectively. Conclusion. Usage of T-SPOT.TB in HD patients with negative TST may enhance diagnosis of LTBI.
Keywords: haemodialysis; interferon-gamma release test; tuberculin skin test; tuberculosis; T-SPOT.TB; GAMMA-RELEASE ASSAYS; MYCOBACTERIUM-TUBERCULOSIS; BOOSTER PHENOMENON; BCG; ENUMERATION; CHILDREN; VACCINES; CONTACT; ELISPOT; UREMIA